The crystal structure of diphenyl bis(2-((diphenoxyphosphoryl)amino)ethyl)phosphoramidate monohydrate C40H42N3O10P3 - Du Chao-Jun; Cai Bin; Li Dan-Xia (Zeitschrift für Kristallographie - New Crystal Structures)
C40H42N3O10P3, monoclinic, P21 (no. 4), a = 9.1649(2) Å, b = 17.1144(3) Å, c = 13.3495(3) Å, β = 109.548(2)°, V = 1973.20(7) Å3, Z = 2, R gt(F) = 0.0559, wR ref(F 2) = 0.1505, T = 99.99(10) K.